Involvement of a vitronectin-like protein in attachment of Agrobacterium tumefaciens to carrot suspension culture cells. - Wagner, V T (1992)
Infections of dicotyledonous plants by Agrobacterium tumefaciens result in the formation of crown gall tumors. Attachment of the bacteria to plant host cells is required for tumor formation. Human vitronectin and antivitronectin antibodies both inhibited the binding of A. tumefaciens to carrot cells. Wild-type bacteria are able to bind radioactive vitronectin; nonattaching mutants showed a reduction in the ability to bind vitronectin. The binding of biotype 1 A. tumefaciens to carrot cells or to radioactive vitronectin was not affected by high ionic strength. Detergent extraction of carrot cells removed the receptor to which the bacteria bind. The extract was found to contain a vitronectin-like protein. These results suggest that A. tumefaciens utilizes a vitronectin-like protein on the plant cell surface as the receptor for its initial attachment to host cells.